Biodiversity, agroecology and nutrition: An educational primer - Gonsalves, Julian; Morada, Jhon Christian; Monville Oro, Emilita; Hunter, Danny; Nabuuma, Deborah; Huynh Thi, Tuyen Thanh; Anunciado, Ma. Shiela; del Rio, Susan; Umali, Diana Jean (2025)
The decline of agrobiodiversity, resulting from a heavy reliance on industrial approaches to transforming agriculture, has affected human diets, the environment, agro-ecosystems, and local food systems. Agricultural biodiversity is fundamental for human and ecosystems health. There are numerous platforms for transforming schools, communities, and landscapes into diverse and healthy landscapes that meet both human and planetary health goals. This educational primer is based on desk research (with key messages and links listed on each page) and is targeted to program planners, designers, and development administrators.